Law Enforcement on The Misuse of "Brong" Exhaust Pipes in The Community Within The Jurisdiction of Bali Regional Police - Putra, I Made Dwiseptya Wiranta; Sihotang, Erikson; Arjawa , Anak Agung Gde Putra (Journal Of Social Science (JoSS), 2025)
The Law Enforcement carried out by the Bali Regional Police in handling the use of brong exhausts is by enforcing traffic regulations, conducting compliant operations, providing services to the community, conducting patrols, conducting raids, and the Bali Regional Police also provide appeals regarding violations or driving regulations in the form of socialization to schools and the community and also providing appeals to shops selling brong exhausts not to sell brong exhausts. The obstacles for the Bali regional police in preventing violations by two-wheeled motor vehicle drivers that occur in their jurisdiction are internal and external obstacles. There are three internal obstacles experienced by the Bali Regional Police Traffic Police, including lack of socialization to the community, limited budget and lack of facilities and infrastructure. In addition to internal obstacles, there are also three external obstacles including lack of cooperation between the traffic police and other agencies related to traffic, low level of legal awareness of two-wheeled motor vehicle drivers, and also non-compliance by drivers with applicable regulations because there are always those who violate them. From these obstacles, the police continue to strive as their obligation to create a safe situation and condition for all parties.